Screening for the metabolic side effects of antipsychotic medication: findings of a 6-year quality improvement programme in the UK. Issue 10 (1st October 2015) - Barnes, T R E; Bhatti, S F; Adroer, R; Paton, C
Abstract : Objectives: To increase the frequency and quality of screening for the metabolic syndrome in people prescribed continuing antipsychotic medication. Design: An audit-based, quality improvement programme (QIP) with customised feedback to participating mental health services after each audit, including benchmarked data on their relative and absolute performance against an evidence-based practice standard and the provision of bespoke change interventions. Setting: Adult, assertive outreach, community psychiatric services in the UK. Participants: 6 audits were conducted between 2006 and 2012. 21 mental health Trusts participated in the baseline audit in 2006, submitting data on screening for 1966 patients, while 32 Trusts participated in the 2012 audit, submitting data on 1591 patients. Results: Over the 6 years of the programme, there was a statistically significant increase in the proportion of patients for whom measures for all 4 aspects of the metabolic syndrome had been documented in the clinical records in the previous year, from just over 1 in 10 patients in 2006 to just over 1 in 3 by 2012. The proportion of patients with no evidence of any screening fell from almost ½ to 1 in 7 patients over the same period. Conclusions: The findings suggest that audit-based QIPs can help improve clinical practice in relation to physical healthcare screening. Nevertheless, they also reveal that only a minority of community psychiatric patients prescribed antipsychotic medication is screened for the metabolic syndrome in accordance with best practice recommendations, and therefore potentially remediable causes of poor physical health remain undetected and untreated.